Effects of Water Exercise on Knee Movement after Postoperative Knee Replacement Surgery in Elderly Female Patients’ Maha Sarakham Province - Srimuang, Tanawanaphorn (Journal of Education Rajabhat Maha Sarakham University, 2020)
The purposes of this research were: 1) study the change, and 2) compare the value of the movement range of knee joint flexion, the circumference of the knee, pain level and 16-foot walk-back period between the water exercise group and the on-land exercise group, and 3) compare the effect of changes in knee with continuous passive movement (CPM) group. The target population was elderly patients over 60 years old with first-stage artificial knee surgery at Maha Sarakham hospital they were divided into 2 groups, which were 10 exercising in water and followed by CPM exercise and 10 exercising on-land and followed by CPM exercise. The instruments were water-based exercise program and the on-land exercise program. The data were analyzed by using two - way ANOVA. The research revealed that: 1) Comparison between the water-based exercise group and the on-land exercise group in female patients after first term surgery found that there overall was statistically significant at 0.05 level and 2) Comparison of percentage change in mean using CPM’s machine there overall was statistically significant at 0.05, and 3) The percentage change in mean of pain level was statistically significant at 0.05 level.